Download presentation

Presentation is loading. Please wait.

Published byCornelius Hampton Modified over 8 years ago

1
8.5 – Using Properties of Logarithms

2
Product Property:

3
Product Property: log b mn

4
Product Property: log b mn = log b m

5
Product Property: log b mn = log b m + log b n

6
Ex.

7
Product Property: log b mn = log b m + log b n Ex. log 9 5x

8
Product Property: log b mn = log b m + log b n Ex. log 9 5x = log 9 5

9
Product Property: log b mn = log b m + log b n Ex. log 9 5x = log 9 5 + log 9 x

10
Product Property: log b mn = log b m + log b n Ex. log 9 5x = log 9 5 + log 9 x Quotient Property:

11
Product Property: log b mn = log b m + log b n Ex. log 9 5x = log 9 5 + log 9 x Quotient Property: log b m n

12
Product Property: log b mn = log b m + log b n Ex. log 9 5x = log 9 5 + log 9 x Quotient Property: log b m = log b m n

13
Product Property: log b mn = log b m + log b n Ex. log 9 5x = log 9 5 + log 9 x Quotient Property: log b m = log b m - log b n n

14
Product Property: log b mn = log b m + log b n Ex. log 9 5x = log 9 5 + log 9 x Quotient Property: log b m = log b m - log b n n Ex.

15
Product Property: log b mn = log b m + log b n Ex. log 9 5x = log 9 5 + log 9 x Quotient Property: log b m = log b m - log b n n Ex. log 9 x 9

16
Product Property: log b mn = log b m + log b n Ex. log 9 5x = log 9 5 + log 9 x Quotient Property: log b m = log b m - log b n n Ex. log 9 x = log 9 x 9

17
Product Property: log b mn = log b m + log b n Ex. log 9 5x = log 9 5 + log 9 x Quotient Property: log b m = log b m - log b n n Ex. log 9 x = log 9 x – log 9 9 9

18
Product Property: log b mn = log b m + log b n Ex. log 9 5x = log 9 5 + log 9 x Quotient Property: log b m = log b m - log b n n Ex. log 9 x = log 9 x – log 9 9 9 Power Property:

19
Product Property: log b mn = log b m + log b n Ex. log 9 5x = log 9 5 + log 9 x Quotient Property: log b m = log b m - log b n n Ex. log 9 x = log 9 x – log 9 9 9 Power Property: log b m p

20
Product Property: log b mn = log b m + log b n Ex. log 9 5x = log 9 5 + log 9 x Quotient Property: log b m = log b m - log b n n Ex. log 9 x = log 9 x – log 9 9 9 Power Property: log b m p = plog b m

21
Product Property: log b mn = log b m + log b n Ex. log 9 5x = log 9 5 + log 9 x Quotient Property: log b m = log b m - log b n n Ex. log 9 x = log 9 x – log 9 9 9 Power Property: log b m p = plog b m

22
Product Property: log b mn = log b m + log b n Ex. log 9 5x = log 9 5 + log 9 x Quotient Property: log b m = log b m - log b n n Ex. log 9 x = log 9 x – log 9 9 9 Power Property: log b m p = plog b m Ex.

23
Product Property: log b mn = log b m + log b n Ex. log 9 5x = log 9 5 + log 9 x Quotient Property: log b m = log b m - log b n n Ex. log 9 x = log 9 x – log 9 9 9 Power Property: log b m p = plog b m Ex. log 9 x 7

24
Product Property: log b mn = log b m + log b n Ex. log 9 5x = log 9 5 + log 9 x Quotient Property: log b m = log b m - log b n n Ex. log 9 x = log 9 x – log 9 9 9 Power Property: log b m p = plog b m Ex. log 9 x 7 = 7log 9 x

25
Ex. 2 Solve the following equations. a. 3 log 5 x – log 5 4 = log 5 16

26
Ex. 2 Solve the following equations. a. 3 log 5 x – log 5 4 = log 5 16 log 5 x 3 – log 5 4 = log 5 16

27
Ex. 2 Solve the following equations. a. 3 log 5 x – log 5 4 = log 5 16 log 5 x 3 – log 5 4 = log 5 16 log 5 x 3 = log 5 16 4

28
Ex. 2 Solve the following equations. a. 3 log 5 x – log 5 4 = log 5 16 log 5 x 3 – log 5 4 = log 5 16 log 5 x 3 = log 5 16 4

29
Ex. 2 Solve the following equations. a. 3 log 5 x – log 5 4 = log 5 16 log 5 x 3 – log 5 4 = log 5 16 log 5 x 3 = log 5 16 4 x 3 = 16 4

30
Ex. 2 Solve the following equations. a. 3 log 5 x – log 5 4 = log 5 16 log 5 x 3 – log 5 4 = log 5 16 log 5 x 3 = log 5 16 4 x 3 = 16 4 x 3 = 64

31
Ex. 2 Solve the following equations. a. 3 log 5 x – log 5 4 = log 5 16 log 5 x 3 – log 5 4 = log 5 16 log 5 x 3 = log 5 16 4 x 3 = 16 4 x 3 = 64 x = 4

32
b. log 4 x – log 4 (x – 6) = 2

33
log 4 x = 2 x – 6

34
b. log 4 x – log 4 (x – 6) = 2 log 4 x = 2 x – 6 Change to exponential form!!!

35
b. log 4 x – log 4 (x – 6) = 2 log 4 x = 2 x – 6 4 2 = x x – 6

36
b. log 4 x – log 4 (x – 6) = 2 log 4 x = 2 x – 6 4 2 = x x – 6 16 = x x – 6

37
b. log 4 x – log 4 (x – 6) = 2 log 4 x = 2 x – 6 4 2 = x x – 6 16 = x 1 x – 6

38
b. log 4 x – log 4 (x – 6) = 2 log 4 x = 2 x – 6 4 2 = x x – 6 16 = x x – 6 16(x – 6) = x

39
b. log 4 x – log 4 (x – 6) = 2 log 4 x = 2 x – 6 4 2 = x x – 6 16 = x x – 6 16(x – 6) = x 16x – 96 = x

40
b. log 4 x – log 4 (x – 6) = 2 log 4 x = 2 x – 6 4 2 = x x – 6 16 = x x – 6 16(x – 6) = x 16x – 96 = x 15x = 96

41
b. log 4 x – log 4 (x – 6) = 2 log 4 x = 2 x – 6 4 2 = x x – 6 16 = x x – 6 16(x – 6) = x 16x – 96 = x 15x = 96 x = 96/15

42
b. log 4 x – log 4 (x – 6) = 2 log 4 x = 2 x – 6 4 2 = x x – 6 16 = x x – 6 16(x – 6) = x 16x – 96 = x 15x = 96 x = 96/15 x = 32/5

Similar presentations

© 2023 SlidePlayer.com Inc.

All rights reserved.

To make this website work, we log user data and share it with processors. To use this website, you must agree to our Privacy Policy, including cookie policy.

Ads by Google